Determination of the Maximal Lactate Steady State Speed of Trotting in Crossbred Native Thai Ponies - Thawornpattanapong, Pattanaporn; Laikul, Aree; Phetudomsinsuk, Kanittha; Pathomsakulwong, Watcharapol; Phanusaweeku, Nuttapon; Cherdchutham, Worakij (Journal of Mahanakorn Veterinary Medicine, 2016)
The purpose of this study aimed to determined maximal lactate steady state speed (MLSS) of the 6 crossbred native Thai ponies (CNTP). Blood lactate concentrations during different velocity of protocols were evaluated. The MLSS in CNTP was 15±1.1 km/h which did not accumulate of blood lactate. Compared mean lactate minimum speed (LMS) and comparison with 10% above LMS, found significant different lactate concentration (P<0.05) at 4, 6, 8 and 10 km. distance indicating that LMS was absolute MLSS (mean MLSS lactate was 1.8±0.2 mmol/L). The average peak blood lactate (LP) was 8.0±1.1 mmol/L. The mean of lactate peak time was 1±0 min. after the exercise test, and mean of the time to base lactate was 71.7±9.8 min. In conclusion, the MLSS of CNTP (15±1.1 km/h) was proposed from this study that would be beneficial for tailoring the exercise program of this type of equids in Thailand.